ANALISIS PENGAKUAN, PENGUKURAN, DAN PELAPORAN PENDAPATAN BERDASARKAN PSAK NO.23 PADA CV. ANUGERAH PLASTERINDO - Sania Bela; Yuli Ermawati (Jurnal Ekonomi, Bisnis dan Social, 2024)
This study aims to analyze methods of recognition, measurement, ncome reporting on CV. Anugerah Plasterindo Surabaya with PSAK No. 23. The research method used s comparative descriptive using primary data taken with nterview techniques and direct observation with managers and logistics administration staff. The results of this study concluded that CV. Anugerah Plasterindo Surabaya recognizes revenue as a result of Galfalum and Ceiling sales and nstallation services based on the cash base concept. CV. Anugerah Plasterindo Surabaya does not record transactions that occur before cash s received by the company, thus causing receivables cannot be definitively known by the company which results n trade receivables will be reported lower than what actually happened. CV measurement. Anugerah Plasterindo Surabaya has not ncluded accounting policies n revenue recognition, which s still based on the cash base method, which n service sales and recording s carried out when cash has been received by the company. So that the company has not followed generally accepted accounting standards that cause disclosure n every transaction on the ncome statement s not significant. ts financial reporting only presents the ncome Statement and balance sheet applied n CV. Anugerah Plasterindo Surabaya s not n accordance with PSAK No. 23.